Городища скіфського часу середньої течії р. Сейм - Каравайко, Д.В. (Археологія, 2023)
У статті представлено загальну характеристику
городищ скіфського часу в басейні середньої течії
р. Сейм. Розглянуто особливості влаштування оборонних споруд. В окрему групу виділено пам’ятки
без виразного культурного шару та нечисленними
знахідками. Попри різні версії, їх призначення залишається під питанням. У загальних рисах висвітлено матеріальний комплекс. Despite many years of studies of the Scythian Age hillforts of the Seim River Putyvl region, their research has only just begun.
This is largely the merit of the works of the Putyvl archaeological expedition, which surveyed all the fortified settlements of the
region during 2012—2016. New topographic plans were created, the peculiarities of the cultural layer of a particular settlement
were clarified. The research conducted allows identifying the general characteristics of the fortified settlements of the region.
All the hillforts are located on promontories, with one or more ramparts on the field side. A characteristic feature is the
presence of two or more sharp ridges, which gently descend to the floodplain. Minor studies of defensive structures were
conducted only at three sites. The presence of a defensive ditch is assumed, although it can be traced only visually at two sites.
In addition, a significant part of the hillforts is fortified by slopes.
Based on the cultural layer we can distinguish three groups: the fortified settlement with a thick layer which has existed for
a long time; the fortified settlement with a layer approximately 0.5 m thick; the fortified settlement with a thin layer and a small
number of finds and objects. The latter are probably unfinished hillforts or administrative centres, combining several unfortified
settlements.
A comprehensive research of the material complex, given the small number of finds, is impossible. However, even with a
superficial analysis there can be traced the connection of the Middle Seim tribes with the Yukhniv population of the forest belt.
It is possible to assume the presence of mixed marriages, which led to the appearance of specific forms of ceramic vessels and
some items in the population of the northern part of the Left Bank forest-steppe.
The question about the time of existence of the sites in the Seim River Putyvl region remains open. Preliminarily we can
speak about the middle of the 6th—4th centuries BC. However, in the 4th century BC there was only one fortified settlement –
Shyriaievе.